S68 Phase 1 trial of an intranasal respiratory syncytial virus (rsv) subunit candidate vaccine: safety results from the muc-syngem study. (15th November 2017) - Vlachantoni, I; Ascough, S; Grimaldi, R; Leenhouts, K; Chiu, C; Openshaw, P
Abstract : Background: RSV is a ubiquitous pathogen causing severe disease in children and the elderly. There is as yet no licensed vaccine. SynGEM, a novel intranasal subunit vaccine based on the RSV F glycoprotein linked to an immunostimulatory bacterium-like-particle carrier, was previously shown in animal models to elicit durable immune responses both locally (nasal secretory IgA) and systemically (serum neutralising antibodies). Induction of mucosal as well as systemic antibodies may enhance protection and reduce transmission. This was the first-in-human phase 1 study of SynGEM in healthy volunteers. Methods: MUC-SynGEM-001 was a randomised, placebo-controlled, phase 1 trial that enrolled healthy adults aged 18–49 years to evaluate the safety and tolerability of SynGEM. Forty-eight participants were randomly assigned to either the low-dose (140 µg F-protein-FP/2 mg BLPs) or high-dose group (350 µg F-protein-FP/5 mg BLPs) and received the vaccine or placebo in a 3:1 ratio. Primary safety outcomes included local or systemic, solicited or unsolicited adverse events (AE) within 28 days and incidence of vaccine-related serious adverse events (SAE) within 57 and 180 days post-vaccination. Antibodies were measured at baseline, day 29 and day 57. Results: Overall incidence of solicited local (83.3% vs 83.3% vs 83.3%) and systemic (88.9% vs 72.2% vs 75.0%) AEs was similar between low-dose, high-dose and placebo groups. Most were of mild severity and only one was severe in a subject subsequently diagnosed with PCR-confirmed influenza A at the time of vaccination. The most common local side effects included nasal discomfort, rhinorrhea and loss of smell whereas fatigue, headache and myalgia were the most frequent systemic effects. Unsolicited AEs were primarily respiratory and reported by 33.3%, 55.6% and 33.3% of participants in the three respective groups. One SAE possibly related to the vaccine was recorded: a high-dose group participant reported persistent pulsatile tinnitus arising after the prime vaccination. Assessment of immunogenicity revealed significant dose-dependent increases in serum and nasal antibodies. Conclusion: SynGEM was generally well tolerated and the data showed that both local and systemic antibodies could be induced by intranasal delivery. However, one SAE was noted and further investigation as to whether intranasal subunit vaccination could be causal is required.